Professional Samples in the Training Process of Primary School Teachers for Working with Inclusion - Bruk Z.Y; Patrusheva I.V; Fedina L.V (Moscow State University of Psychology and Education, 2018)
The article presents the results of professional sample as one of the conditions of practice-oriented learning. The samples were carried out during the approbation of the project which is aimed at the improving of future teacher's training through strengthening of the practical orientation in the context of inclusive education. The authors describe the content and mechanism of a professional sample in the real teaching and educational process by the implementation of the module "Theoretical and methodological foundations of inclusive education". The authors came to the conclusion that the use of professional samples in the system of future teachers training can significantly increase the indicators of methodical readiness of students. Nevertheless, the competences of diagnosing the teaching and educational process, the ability to conduct observations are not sufficiently formed. The use of the professional samples method in the educational process helps to connect theory and the practical activity of the teacher in the context of inclusive education, to develop the competence of making informed and effective decisions, to form the experience of interaction with special children, and to develop personal responsibility and the ability to self-reflection.